If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11(x+7)=5(6x-8)-6x
We move all terms to the left:
11(x+7)-(5(6x-8)-6x)=0
We multiply parentheses
11x-(5(6x-8)-6x)+77=0
We calculate terms in parentheses: -(5(6x-8)-6x), so:We get rid of parentheses
5(6x-8)-6x
We add all the numbers together, and all the variables
-6x+5(6x-8)
We multiply parentheses
-6x+30x-40
We add all the numbers together, and all the variables
24x-40
Back to the equation:
-(24x-40)
11x-24x+40+77=0
We add all the numbers together, and all the variables
-13x+117=0
We move all terms containing x to the left, all other terms to the right
-13x=-117
x=-117/-13
x=+9
| 9k-(-3k-7)=15 | | (6x+20)+(2x+4)=0 | | 49=x−48 | | 0.07g-6.5=0.2g | | 2x+56=4x-14 | | 3x-12=6x+5 | | -5x20=100 | | 7p+5p-3p=21+9-10 | | 7a−3=13a+7 | | -4+33=2x+81 | | -6(h+7)+8=-19 | | (6+6x)=-22x+2 | | -26=-10+8k | | (5u+10)=5 | | 4≤x+2≤=8 | | -10n-35=0 | | 8n-(4n+5)=9 | | -3=x-1-3 | | 11+21=-4(6x-8) | | (4n+19)-(6(n-9))=0 | | 83=21+m | | 8(y+2)+2y=-34 | | 5(x-5)=4(x+8) | | 2-6x-2=12 | | 2n+54-19=0 | | 8x-12=-71 | | 4=-2(1-3x)-6(x-1) | | 2+3(x1)=17 | | 1/5*(x-3)=3/4 | | -12=-2(r+5) | | -5/8v=20 | | 2(2-6x)=-68 |